CAN HEPATIC SERUM ALKALiNE PHOSPHATASE BE AN INDICATION FOR CHOLEDOCHUS EXPLORATION? - M. Metin BELVİRANLI and Adil KARTAL and Adnan KAYNAK and Faruk AKSOY and Ömer KARAHAN and Güven BEKDEMİR and Kemal TAYFUR (Turkish Journal of Gastroenterology, 2020)
-